ЕЛЕКТРОФІЗИЧНІ ПРОЦЕСИ ДЕГРАДАЦІЇ ЗШИТОЇ ПОЛІЕТИЛЕНОВОЇ ІЗОЛЯЦІЇ СИЛОВИХ КАБЕЛІВ І САМОУТРИМНИХ ІЗОЛЬОВАНИХ ПРОВОДІВ ПРИ НЕСИНУСОЇДНИХ НАПРУГАХ І СТРУМАХ - Щерба, A.А.; Щерба, М.А.; Перетятко, Ю.В. (Інститут електродинаміки НАН України, Київ, 2023)
The features of electro-physical processes of degradation of cross-linked polyethylene (XLPE) insulation of power cables and self-carrying insulated wires (SIW) are studied, taking into account water microinclusions and dendrite branches that appear in such insulation during manufacture and operation. It is substantiated that the appearance of non-sinusoidal voltages and currents in power transmission lines (TL) using modern power cables and SIW with solid XLPE insulation causes an increase in electro-physical factors aimed at increasing the pulsating electromechanical pressure on the surface of solid XLPE insulation by liquid conductive microinclusions and dendrite branches and an increase in over time, their sizes along the strength of the existing electric field (EF). The paper defines the patterns of change over time in the magnitude of the stressed volume and the maximum pressure in the XLPE insulation and the additional impact on such patterns of higher harmonic components of electrical voltages and currents during non-sinusoidal processes in such insulation. It is indicated that such electro-physical effects on solid polymer insulation lead to an increase in the intensity of both threshold mechanisms and stochastic ones of destruction of the microstructure of the solid XLPE insulation of power cables and self-carrying insulated wires and require the development of additional regulations for standard conditions for their manufacture and operation. References 10, figures 3.